2022
DOI: 10.1039/d1cy02340c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and origin of the stereoselectivity of manganese-catalyzed hydrosilylation of alkynes: a DFT study

Abstract: Manganese catalyzed hydrosilylation reaction provides a powerful platform to synthesize organosilicon compounds due to their rich reserves, low toxicity, and promising novel reactivity. In this work, the detailed mechanisms of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Independent catalytic assays were made with Mn−H and Mn−Si complexes as potential intermediates, but comparable results were attained only with the Mn−Si species. These observations along with a further computational study presented by Li et al 50 serve as evidence for the mechanism presented in Scheme 9A as the plausible pathway for this transformation. On the other hand, they observed that [Mn 2 (CO) 10 ] (Mn-12) favored the formation of hydrosilylated Z-products and hypothesized that this could be occurring through a radical pathway due to the low Mn−Mn bond energy.…”
Section: Hydrosilylation Of Alkynessupporting
confidence: 59%
See 1 more Smart Citation
“…Independent catalytic assays were made with Mn−H and Mn−Si complexes as potential intermediates, but comparable results were attained only with the Mn−Si species. These observations along with a further computational study presented by Li et al 50 serve as evidence for the mechanism presented in Scheme 9A as the plausible pathway for this transformation. On the other hand, they observed that [Mn 2 (CO) 10 ] (Mn-12) favored the formation of hydrosilylated Z-products and hypothesized that this could be occurring through a radical pathway due to the low Mn−Mn bond energy.…”
Section: Hydrosilylation Of Alkynessupporting
confidence: 59%
“…Independent catalytic assays were made with Mn–H and Mn–Si complexes as potential intermediates, but comparable results were attained only with the Mn–Si species. These observations along with a further computational study presented by Li et al serve as evidence for the mechanism presented in Scheme A as the plausible pathway for this transformation.…”
Section: Hydrofunctionalization Of Unsaturated C–c Bondsmentioning
confidence: 99%
“…Zhang et al also examined the reactions between the heavier group 14 hydrides with PhCCH, and they found that both n Bu 3 SiH and n Bu 3 GeH can react smoothly with alkynes to obtain the corresponding products in high yields, whereas for n Bu 3 SnH, no corresponding product be detected. 7 The hydrosilylation mechanism of MeCCMe has been studied by our group, 29 and the mechanisms of hydrosilylation and hydrogermylation are similar; both contain two HAT processes and a radical transformation process. The radical transformation process is the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
“…Under light irradiation, those catalyzed by Mn 2 (CO) 10 and Fe 2 Cp(CO) 4 follow the radical transfer mechanism. 29–32 Among the transition metal catalysts, manganese is very abundant on the earth 33 and its binuclear manganese complex Mn 2 (CO) 10 has the advantages of low price and easy availability, but the study of the hydrofunctionalization of alkynes using manganese catalysts is still in its infancy. 29,30 It is believed that the homolysis of the Mn–Mn bond induced by visible light is easy because the bond dissociation energy (BDE) of the Mn–Mn bond is low, only 15.0 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation